Inducible laryngeal obstruction: an official joint European Respiratory Society and European Laryngological Society statement - Halvorsen, Thomas; Herth, Felix (The European respiratory journal, 2017)
Inducible laryngeal obstruction (ILO) describes an inappropriate, transient, reversible narrowing of the larynx in response to external triggers. ILO is an important cause of a variety of respiratory symptoms and can mimic asthma. Current understanding of ILO has been hampered by imprecise nomenclature and variable approaches to assessment and management. A task force of the European Respiratory Society (ERS) and European Laryngological Society (ELS) was thus set up to address this, and to identify research priorities.
Gesehen am 24.05.2018